2020
DOI: 10.1016/j.ijid.2020.05.013
|View full text |Cite
|
Sign up to set email alerts
|

HIV care in times of the COVID-19 crisis — Where are we now in Central and Eastern Europe?

Abstract: Conclusions: A shortage of resources is evident, with an impact on HIV care inevitable. We need to prepare to operate with minimal medical resources, with the aim of securing constant supplies of ART. Nongovernmental organizations should re-evaluate their earlier objectives and support efforts to ensure continuity of ART delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
88
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 8 publications
7
88
0
13
Order By: Relevance
“…The fear of contracting COVID-19 has led to decreased engagement with care among PLWH in several countries [ [39] , [40] , [41] , [42] ]. The reasons for this are unsurprising- people who have faced stigma for decades due to their HIV status and live under the burden of a chronic virus are hesitant to engage in care when the prospect of being infected with another, more deadly virus is real.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fear of contracting COVID-19 has led to decreased engagement with care among PLWH in several countries [ [39] , [40] , [41] , [42] ]. The reasons for this are unsurprising- people who have faced stigma for decades due to their HIV status and live under the burden of a chronic virus are hesitant to engage in care when the prospect of being infected with another, more deadly virus is real.…”
Section: Resultsmentioning
confidence: 99%
“…The rapidly growing pandemic has strained national healthcare systems worldwide. In Eastern Europe, HIV physicians have been called to care for patients with COVID-19, creating staffing shortages [ 39 ]. This has forced some clinics to suspend in-person visits, others to postpone blood tests, and some to solely focus on ART distribution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 poses a particular challenge for the African continent because of existing high prevalence rates of other infectious diseases including human immunodeficiency virus (HIV)/ acquired immunodeficiency syndrome (AIDS), TB, cholera, and malaria, along with high rates of AMR and a disproportionate burden of poverty ( UNAIDS, 2019 ; World Health Organisation, 2019 ; WHO, 2019a ; Ataguba, 2020 ; Godman et al., 2020a ; Simpson, 2020 ; United Nations Economic Commission for Africa, 2020a ; WHO, 2020b ; WHO, 2020c ), with ongoing infectious disease initiatives appreciably challenged by COVID-19 ( Mendelson and Matsoso, 2015 ; Ghana Ministry of Health, 2018 ; Godman et al., 2020a ; Kowalska et al., 2020 ). The presence of multi-morbidity with NCDs will aggravate the situation further ( Oni et al., 2015 ; So-Armah and Freiberg, 2018 ; Achwoka et al., 2019 ; Chang et al., 2019 ; Kansiime et al., 2019 ; Woldesemayat, 2020 ), with already high rates of CVD and diabetes a growing concern across Africa ( Mensah et al., 2015 ; Godman et al., 2020b ; Godman et al., 2020c ).…”
Section: Introductionmentioning
confidence: 99%
“…One survey conducted among 19 countries in Central and Eastern Europe reported that HIV clinics were normally operating in only six of these countries (∼32%) during the pandemic. In 11 countries (∼58%), health providers had dual duties for HIV and COVID-19 care (Kowalska et al, 2020). One study conducted among people living with HIV (PLWH) in Atlanta, the United States suggested that responses to COVID-19 such as social distancing were associated with increased cancelations of HIV care appointment (Kalichman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%